Effect of oil price fluctuations on the components of total spending in Saudi Arabian economy during the period 2000-2018: Empirical study - Mohamed, Fatma Ahmed Hasan (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to analyze the relationship between oil price changes and all components of total spending in the Kingdom of Saudi Arabia during the period 2000-2018, to determine which of the spending components are most related to oil price changes and to evaluate the performance of the financial policy followed in the Kingdom during that period, and the study used both approaches analytical descriptive and standard approach to achieve this goal, and the study found an average direct correlation of (0.52) between changes in average oil and government final consumption spending, and a moderate direct correlation also between average oil prices and private consumption spending of (0.43). And a moderate to strong positive relationship between average oil prices and government investment spending estimated at (0.65), and a moderate to strong inverse relationship between average oil prices and external spending in the Kingdom, estimated at (-0.67), and the study demonstrated the existence of a direct causal relationship between oil price changes. The study also demonstrated the government's final consumption spending in the Kingdom in the short term, using Granger tests of causation, With no direct causal relationship in the short term between average oil prices and the rest of the components of total spending, and by using simple linear regression analysis between each of the average oil prices as an independent variable and between all spending components as variables separately to test the relationship in the long term, it is proved that oil prices explain Simple to moderate changes in the components of total spending, which indicates that the Kingdom, like most oil-producing countries, has adopted, during the past few decades, anti-economic financial policies, away from the negative effects of instability of oil prices, especially with regard to investment spending, which in turn is reflected in the completion of Continuous successive development plans and maintaining near-sustainable economic growth rates.
Keywords: oil prices; types of spending; Saudi Arabia